Proceso de ASC - ASTROFOTOGRAFIA Y DIVULGACION ASTRONOMICA DENTRO DE LA UNIVERSIDAD EAFIT (2020)
Since time immemorial, humans have felt a great cuRíosity about the stars, a cuRíosity that, like science, has not remained static over time but has continuously advanced and developed. This enduring cuRíosity and scientific progress have given rise to astronomy, providing a broad knowledge base and laying new foundations for further advancement. It is for this reason that the research group wants to contribute its grain of sand. Building on previous projects, the Quasar research group has acquired a special camera that can be attached to the university’s telescope. This allows for the acquisition and recording of astronomical images useful for research and dissemination. The group aims to use this equipment to conduct astronomical observations and photography, making the results public so that people outside the group can experience this firsthand. This is expected to spark their cuRíosity about these topics, potentially seeing joining the research group as an opportunity to expand their knowledge and answer questions about these subjects. Similarly, with the same goal of inviting participation in the research group, there are plans to hold a series of short talks on intriguing astronomy topics that are both attention-grabbing and highly informative.